2005
DOI: 10.1039/b405486e
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and mass transport enhancement effects on rates of styrene epoxidation catalyzed by myoglobin films in microemulsions

Abstract: Biocatalytic surfaces hold promise for future clean methods of chemical synthesis. Biocatalyst films utilizing inexpensive redox proteins can operate in low-toxicity microemulsions with high capacities to dissolve nonpolar reactants. Crosslinked films of myoglobin (Mb) and poly(L-lysine) (PLL) attached to oxidized carbon cathodes gave up to 40-fold larger turnover rates in bicontinuous microemulsions compared to o/w microemulsions and micelles. Larger synthetic turnover rates are correlated with up to 10-fold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…6,8 Fluorescence probe studies with pyrene in Mb-PLL films exposed to microemulsions showed that the pyrene residence site in CTAB microemulsions is somewhat more polar than the residence site in films that are exposed to SDS microemulsions. 9 Pyrene sites in both systems were more polar than a hydrocarbon environment but much less polar than water. Because the vicinal dibromides in the present study are relatively nonpolar, we assume that they reside in the films in regions similar to the pyrene residence sites.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…6,8 Fluorescence probe studies with pyrene in Mb-PLL films exposed to microemulsions showed that the pyrene residence site in CTAB microemulsions is somewhat more polar than the residence site in films that are exposed to SDS microemulsions. 9 Pyrene sites in both systems were more polar than a hydrocarbon environment but much less polar than water. Because the vicinal dibromides in the present study are relatively nonpolar, we assume that they reside in the films in regions similar to the pyrene residence sites.…”
Section: Discussionmentioning
confidence: 92%
“…SDS entering into the cationic PLL films was revealed previously from quartz crystal microbalance (QCM) studies of PLL films containing cobalt corrin catalysts 23 and by preliminary studies of Mb-PLL films. 9 Here we provide more detailed QCM results for Mb-PLL films made on gold-coated quartz QCM resonators and then immersed in the CTAB and SDS microemulsions. In QCM, the change in frequency (-∆F) for dry films is proportional to mass per unit area (M/A) in the absence of viscoelasticity changes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated control of catalytic activity with microemulsion composition for adsorbed FeMb films [14]. More recently we made crosslinked films of FeMb-PLL that were stable in microemulsions and studied the factors important for efficient catalysis [15,16]. Given this background, we sought to combine the catalytic activity of the cobalt corrin surrounded by protein envelope with the reactivity control of microemulsions.…”
Section: Introductionmentioning
confidence: 98%